The recent advances in the nanotechnology and its applications in food processing : a review. - Abbas, Kassim Ali; Saleh, Adel M.; Mohamed, Aminuddin Rizan; N., Mohd Azhan (WFL Publisher, 2009)
The objectives of this paper was to discuss the latest development of nanotechnology, especially in food industries, to give clearer picture about the effect of nanotechnology in food industries and to highlight the latest applications of nanotechnology in food processing industry. However, the risk issues involving the use of nanotechnology in food were also explored. The outcome of this research revealed that the nanotechnology could be useful for controlling and manipulating the matter at the nanoscale level during processing. On the other hand, nanotechnology could also help the consumers to modify the food depending on their own nutritional needs and tastes. However, from health viewpoint, the potential risks of nanoscale materials and the possibility of the accumulation and translocation of nanoparticles in the body should be avoided.